Frequency and Intensity of Nurses\' Confrontation with Intra and Extra-Organizational Factors Governing Burn Centers - Forough Rafii; Seyedeh Fatemeh Haghdoost Oskouie; Fahimeh Mohammadi Fakhar; Mohammadreza Zarei; Hamid Haghani (Tehran University of Medical Sciences, 2012)
Background & Aim: Multiple structural factors preside over burn units influence nurses&apos quality of care and their activities. The complexity and multy-dimensional nature of nursing care in these units, creates many challenges. Understanding the perspectives of people&aposs involved is recommended. This study, with a theory-to-research approach, was conducted to assess the frequency of confronting intra and extra organizational factors preside over burn units, the intensity of its related pressure, and correlations among these variables from nurses&apos perspectives. Methods & Materials: In this cross-sectional, correlational study, 98 nurses working in the Shahid Mottahari burn center were recruited by census. Data was collected using the intra and extra organizational factors instrument, provided based on the previous grounded theory study of the researchers. Intra-organizational factors questionnaire consisted of 58 Likert type statements in eight subscales and two dimensions of frequency (α=0.94) and intensity (α=0.96). Extra-organizational factors questionnaire consisted of eight Likert type statements (α=0.74). Data were analyzed using the SPSS version 14. Results: The results revealed that the frequency of nurses&apos confrontation with factors related to environment and patients as well as its intensity were more than other factors. Moreover, the intensity of the whole factors was more than its frequency. All the extra- organizational factors were significantly correlated with all intra-organizational factors except for the "absence of employment permission" (P<0.05). Conclusion: This study explained the importance of intra-organizational factors of a burn center in inducing stress on nurses. In addition to verification of some relationships in the previous mid-range theory, the results of this study also modified some of its aspects. Therefore it added to the existing body of knowledge about organizational factors and job stress in burn units. Moreover, it produced some evidences to use in nursing administration and service, and finally it resulted in some directions to control stress in nurses&apos job.